Effect of Zincate Treatment of As-Cast AZ91 Mg Alloy on Electrodeposition of Copper in a Copper Pyrophosphate Bath - Nguyen, Van Phuong; Park, Min-Sik; Yim, Chang Dong; You, Bong Sun; Moon, Sungmo (Biuletyn Uniejowski, 2016)
In this work, effect of zincate treatment of AZ91 Mg alloy on the following electrodeposition of copper was examined in a non-cyanide bath containing pyrophosphate ions in view of surface morphology and adhesion of the electrodeposited copper layer. Without zincate treatment, the electrodeposited copper layer showed very porous structure and poor adhesion. On the other hand, the copper layer electrodeposited on the zincatetreated surface showed dense structure and good adhesion. The dissolution rate of AZ91 Mg alloy after the zincate treatment appeared to decrease about 40 times in the copper pyrophosphate bath, as compared to that of the surface without zincate treatment. The porous morphology and poor adhesion of a copper layer on the AZ91 Mg alloy surface without zincate treatment were attributed to small number of nucleation sites of copper because of rapid dissolution of the magnesium substrate in the pyrophosphate bath. Based on the experimental results, it is concluded that the zincate treatment to form a conducting and protecting layer on the AZ91 Mg alloy surface is essential for successful electrodeposition of a copper layer on AZ91 Mg alloy with good adhesion and dense structure in the copper pyrophosphate bath. KCI Citation Count: 1